1963
DOI: 10.1128/jb.86.6.1301-1307.1963
|View full text |Cite
|
Sign up to set email alerts
|

ROLES OF CITRATE AND ACETOIN IN THE METABOLISM OF STREPTOCOCCUS DIACETILACTIS

Abstract: tococcus diacetilactis was unable to use citrate as a source of energy for growth, but the addition of citrate to a lactose-containing medium increased the specific growth rate 35%. Besides serving as the precursor of acetoin, some of the pyruvate formed from citrate was incorporated into cell material, primarily into lipids. A constant fraction of the weight of new cells was synthesized from the pyruvate formed from citrate. The rate of entry of citrate into cells was independent of the growth rate, and the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
29
1
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(42 citation statements)
references
References 4 publications
11
29
1
1
Order By: Relevance
“…Strains of Lactobacillus casei, L. plantanrm, and L. brevis can use citrate for energy in the absence of carbohydrates (Fryer, 1970;Peterson and Marshall, 1990). Harvey and Collins (1963) showed that Lactococcus la& subsp. diacetylactis was unable to use citrate as an energy source for Volume 58, No.…”
Section: Ournalmentioning
confidence: 99%
“…Strains of Lactobacillus casei, L. plantanrm, and L. brevis can use citrate for energy in the absence of carbohydrates (Fryer, 1970;Peterson and Marshall, 1990). Harvey and Collins (1963) showed that Lactococcus la& subsp. diacetylactis was unable to use citrate as an energy source for Volume 58, No.…”
Section: Ournalmentioning
confidence: 99%
“…Media. The partially defined, lipoic acid-free medium used to grow S. diacetilactis was the same as that reported by Harvey and Collins (15), except that 0.4% glucose replaced lactose, citrate was omitted, the casein hydrolysate content was increased to 0.2%, pantothenate (1.0 ,g/ml) and pyridoxal (1.2 ;g/ml) were included, and the medium was adjusted to pH 6.8. [It has been reported that some casein hydrolysates have low levels of methionine (1), but addition of DL-methionine (1.0 ug/ml) to the basal medium did not enhance the growth of S.…”
mentioning
confidence: 99%
“…The supernatant fluid was decanted, dialyzed against 100 volumes of 0.01 M Tris-cysteine buffer (pH 7.0) for 24 hr at 4 C, and stored at 0 or -20 C. For certain indicated experiments, the extracts were treated with anion-exchange resin (acid-washed Dowex 1-X2) to remove CoA (3). [This procedure also removes oxalacetate decarboxylase (15).] Analytical procedures.…”
mentioning
confidence: 99%
“…Although S. lactis ssp. diacetilactis is unable to utilize citrate as an energy source, its addition to a lactose containing medium increases the specific growth rate up to 35% [73]. It should be pointed out that pyruvate formed through the citrate fermentation pathway joins the common acetoin-forming pathway with pyruvate as a central intermediate [74].…”
Section: Physiology and Enzyrnology Of Citrate Metabolismmentioning
confidence: 99%